Pirtobrutinib inhibits wild-type and mutant Bruton’s tyrosine kinase-mediated signaling in chronic lymphocytic leukemia - Burcu Aslan; Gorkem Kismali; Lakesla R. Iles; Ganiraju C. Manyam; Mary L. Ayres; Lisa S. Chen; Mihai Gagea; Maria Teresa Sabrina Bertilaccio; William G. Wierda; Varsha Gandhi (Blood Cancer Journal, 2022)
Abstract Pirtobrutinib (LOXO-305), a reversible inhibitor of Bruton’s tyrosine kinase (BTK), was designed as an alternative strategy to treat ibrutinib-resistant disease that develops due to C481 kinase domain mutations. The clinical activity of pirtobrutinib has been demonstrated in CLL, but the mechanism of action has not been investigated. We evaluated pirtobrutinib in 4 model systems: first, MEC-1, a CLL cell line overexpressing BTKWT, BTKC481S, or BTKC481R; second, murine models driven by MEC-1 overexpressing BTKWT or BTKC481S; third, in vitro incubations of primary CLL cells; and finally, CLL patients during pirtobrutinib therapy (NCT03740529, ClinicalTrials.gov). Pirtobrutinib inhibited BTK activation as well as downstream signaling in MEC-1 isogenic cells overexpressing BTKWT, BTKC481S, or BTKC481R. In mice, overall survival was short due to aggressive disease. Pirtobrutinib treatment for 2 weeks led to reduction of spleen and liver weight in BTKWT and BTKC481S cells, respectively. In vitro incubations of CLL cells harboring wild-type or mutant BTK had inhibition of the BCR pathway with either ibrutinib or pirtobrutinib treatment. Pirtobrutinib therapy resulted in inhibition of BTK phosphorylation and downstream signaling initially in all cases irrespective of their BTK profile, but these effects started to revert in cases with other BCR pathway mutations such as PLCG2 or PLEKHG5. Levels of CCL3 and CCL4 in plasma were marginally higher in patients with mutated BTK; however, there was a bimodal distribution. Both chemokines were decreased at early time points and mimicked BCR pathway protein changes. Collectively, these results demonstrate that pirtobrutinib is an effective BTK inhibitor for CLL harboring wild-type or mutant BTK as observed by changes in CCL3 and CCL4 biomarkers and suggest that alterations in BCR pathway signaling are the mechanism for its clinical effects. Long-term evaluation is needed for BTK gatekeeper residue variation along with pathologic kinase substitution or mutations in other proteins in the BCR pathway.